2011
DOI: 10.4049/jimmunol.1004125
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Suppress In Situ Proliferation of Cytotoxic T Cells by Promoting Differentiation of Gr-1+ Conventional Dendritic Cells through IL-6

Abstract: Cancers are often accompanied by inflammation, which can promote tumor growth, invasion, and metastases. We show that the tumor microenvironment induces the development of a Gr-1+ conventional dendritic cell (cDC) subpopulation that is functionally defective. Gr-1+cDCs differentiated from recruited immediate precursors of cDCs, a process supported by the inflammatory cytokine milieu in tumors. Inhibition of Gr-1+cDC differentiation enhanced intratumor expansion of cytotoxic CD8+ T cells (CTLs), resulting in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…27 Recently, we reported that tumor pre-cDCs rapidly differentiate into proliferating cDCs, and under the influence of the tumor milieu, some of these cells generate a Gr-1 ϩ cDCs subpopulation that induces T-cell anergy. 36 In contrast with DC-d-Ms, Gr-1 ϩ cDCs express CD11c and MHC class II and cannot directly suppress proliferation of T cells stimulated by third-party antigenpresenting cells. Most DC-d-Ms in tumors also express Gr-1, and could be classified as Gr-1 ϩ MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, we reported that tumor pre-cDCs rapidly differentiate into proliferating cDCs, and under the influence of the tumor milieu, some of these cells generate a Gr-1 ϩ cDCs subpopulation that induces T-cell anergy. 36 In contrast with DC-d-Ms, Gr-1 ϩ cDCs express CD11c and MHC class II and cannot directly suppress proliferation of T cells stimulated by third-party antigenpresenting cells. Most DC-d-Ms in tumors also express Gr-1, and could be classified as Gr-1 ϩ MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although their studies supported the importance of monocyte-derived DCs, anti-CD11b Abs deplete both DC2 and DC3. We reported that decreasing the frequency of CD11c + DCs in the CD11c-Cre mouse model reduced intratumor CTL proliferation (17); however, this experimental approach depletes all DCs. Thus, the relevance of pre-cDC-derived versus monocytederived tumor DCs to intratumor CTL responses in vivo has yet to be established.…”
mentioning
confidence: 99%
“…Intratumor DCs also promote the expansion and function of tumor-infiltrating CTLs (17,18); however, controversy persists over which DC subpopulation is involved. Several reports have emphasized the dominance of DC1 based on their robust Ag cross-presenting activity (as compared with DC2 and other myeloid populations) and their apparent importance in inhibiting tumor growth in mice treated with adoptive CTL therapy (18)(19)(20).…”
mentioning
confidence: 99%
“…Within the tumor microenvironment (TME), some cells differentiated into immunosuppressive DCs and macrophages [6,14] . Cancer has no apparent adverse effect on bone marrow, spleen, or circulating pre-cDC [11] , suggesting that tumor DC dysfunction is initiated by direct exposure to the TME.…”
Section: Research Highlightmentioning
confidence: 99%
“…Recent evidence suggests that effective control of cancer also requires restimulation of CTLs by intra-tumor DCs [4][5][6] . Cancer sabotages this process by impairing the function of DCs and by failing to generate or recruit DC subpopulations that possess superior tumor antigen cross-presentation activity, such as CD103 + DC [7,8] .…”
mentioning
confidence: 99%